1993
DOI: 10.1115/1.2906735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Back-Pressure in a Lean Blowout Research Combustor

Abstract: Experimental information is presented on the effects of back-pressure on flame-holding in a gaseous fuel research combustor. Data for wall temperatures and static pressures are used to infer behavior of the major recirculation zones, as a supplement to some velocity and temperature profile measurements using LDV and CARS systems. Observations of flame behavior are also included. Lean blowout is improved by exit blockage, with strongest sensitivity at high combustor loadings. It is concluded that exit blockage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…LBO data were collected by maintaining a constant airflow rate, heating the combustor to a near steady-state temperature at stoichiometric fuel-air ratio, and then gradually decreasing the fuel flow rate until blowout occurred. This is a procedure similar to that adopted by Sturgess et al (1991). The flame length was defined as the distance from the nozzle exit to the flame tip and measured by taking individual color snap-shots of the combustion process, enlarging these photographs, and then carefully plotting the luminous boundary of the flame front.…”
Section: Error Analysismentioning
confidence: 99%
“…LBO data were collected by maintaining a constant airflow rate, heating the combustor to a near steady-state temperature at stoichiometric fuel-air ratio, and then gradually decreasing the fuel flow rate until blowout occurred. This is a procedure similar to that adopted by Sturgess et al (1991). The flame length was defined as the distance from the nozzle exit to the flame tip and measured by taking individual color snap-shots of the combustion process, enlarging these photographs, and then carefully plotting the luminous boundary of the flame front.…”
Section: Error Analysismentioning
confidence: 99%
“…Based on detection of LBO precursors using OH* chemiluminescence, Thiruchengode et al extended the LBO limit by modifying the fuel fraction injected into the flame stabilization zone 10 . Gutmark et al extended the LBO limit of a premixed dump combustor by generating small-scale vortices using shear layer forcing 15 , whereas Sturgess et al found that the LBO limit can be extended by exit blockage 16 . Durbin and Ballal observed that the LBO limit was reduced by increasing the outer swirl intensity if the inner swirl is stronger than the outer swirl 17 .…”
mentioning
confidence: 99%
“…LBO scaling as a function of combustion parameters (incoming flow velocity, equivalence ratio, pressure, temperature, and fuel type) have been reported for specific combustor configurations [9][10][11][12][13][14], and active or passive control strategies to extend LBO have been explored [8,[15][16][17][18]. Several LBO mechanisms have been proposed and include balance between the rate of entrainment of reactants into the recirculation zone and the rate of buming [19], energy balance between heat supplied by the hot recirculating flow to the fresh gases and that released by reaction [20][21][22][23], balance between contact time between the combustible mixture and hot gases in the shear layer and chemical ignition time [20,[24][25][26], and mecha-nisms related to local extinction by excessive flame stretch with a flamelet based description [27][28][29].…”
Section: Introductionmentioning
confidence: 99%